A Study of the Role of Government in Income and Wealth Distribution by Integrating the Walrasian General Equilibrium and Neoclassical Growth Theories - Wei-Bin Zhang (Interdisciplinary Description of Complex Systems, 2014)
This paper proposes a growth model of heterogeneous households with economic structure, wealth accumulation, endogenous labour supply, and tax rates. The paper is focused on effects of redistribution policies on income and wealth distribution, economic structure and economic growth. The paper integrates the Walrasian general equilibrium theory and neoclassical economic growth within a comprehensive framework. We overcome the controversial features in the two traditional theories by applying an alternative approach to households. We build an analytical framework for a disaggregated and microfounded general theory of economic growth with endogenous wealth accumulation. We simulate the model to identify equilibrium, stability and to plot the motion of the dynamic system with three groups. We also carry out comparative dynamic analysis with regard to the lump tax, human capital and propensity to use leisure time.